Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
Franz Joseph Fiord. This photo is taken from the western side of Ymer Island above Blomsterbukta the only bay on that side of the island. In background center, ice cap and glaciers on Suess Island. In background on right colored strata on west side of Franz Josef Fiord SW of Teufelsschloss. Also one of the largest icebergs we saw in this fiord.